Intravenous General Anesthesia for Patients with Neurological Disorders - Kentaro Ouchi (Global Journal of Anesthesiology - Peertechz Publications, 2015)
In dental practice, intravenous general anesthesia is useful for patients who are difficult to treat when not sedated such as those with neurological disorders [1].